PENGARUH PROMOSI, KUALITAS PELAYANAN DAN HARGA PREMI TERHADAP KEPUASAN NASABAH PADA PT. ASURANSI JIWASRAYA (PERSERO) ASC MEDAN UTARA - Sintya Dewi Siahaan; Tirta Nadia Sibarani; Nurmaidah Ginting (Jurnal Manajemen Terapan dan Keuangan, 2021)
This research was conducted to examine the effect of promotions, service quality and premium price on customer satisfaction at PT. Asuransi Jiwasraya (Persero) ASC Medan Utara. In this research, the theory used is promotion, service quality, premi price and customer satisfaction. The research method used is quantitative research methods and the type in this research is descriptive quantitative. The population in this study were customers of PT. Asuransi Jiwasraya (Persero) ASC Medan Utara, totaling 3,734 customers. The sample in this study were 100 customers. In testing the validity and reliability of 30 respondents. The results showed that simultaneously promotion, service quality and premium prices have a positive and significant effect on customer satisfaction at PT. Asuransi Jiwasraya (Persero) Medan Utara. Partially promotion affects customer satisfaction PT.Asuransi Jiwasraya (Persero) ASC Medan Utara and partially service quality affects customer satisfaction PT.Asuransi Jiwasraya (Persero) ASC Medan Utara and the premium price partially affects customer satisfaction of PT.Asuransi Jiwasraya (Persero) ASC Medan Utara. The coefficient of determination obtained is 0.539, which means 53.9% of the variation in customer satisfaction variables which can be explained by variations in promotional variables, service quality and premium price. While the remaining 46.1% is explained by variations in other variables that are not examined. Keywords: Promotion, Service Quality, Premi Price, Customer Satisfaction